GROWTH ANALYSIS OF EPIPREMNUM AUREUM (L.) ENGL. IN RESPONSE TO SALINITY STRESS (International Association of Biologicals and Computational Digest, 2023)
Potted plants of Epipremnum aureum (L.) Engl. were submitted to salinity stress (0, 100 ppm and 500 ppm NaCl irrigation) for 28 days in order to assess the effect on growth parameters viz. Relative Growth Rate (RGR), Net Assimilation Rate (NAR) and Leaf Weight Ratio (LWR). The salt stress caused reduction in LWR, NAR and RGR. It was observed that the effect of salinity was more pronounced on growth parameters at higher concentration than that at lower concentration.
Keywords: Epipremnum aureum (L.) Engl., growth analysis, NaCl, net assimilation rate, relative growth rate, leaf weight ratio